Gene knockdown by structure defined single-stem loop small non-coding RNAs with programmable regulatory activities - Yang Wang; Guobin Yin; Huanjiao Weng; Luyao Zhang; Guocheng Du; Jian Chen; Zhen Kang (Synthetic and Systems Biotechnology, 2023)
Gene regulation by trans-acting small RNAs (sRNAs) has considerable advantages over other gene regulation strategies. However, synthetic sRNAs mainly take natural sRNAs (MicC or SgrS) as backbones and comprise three functional elements folding into two or more stem-loop structures: an mRNA base pairing region, an Hfq-binding structure, and a rho-independent terminator. Due to limited numbers of natural sRNAs and complicated backbone structures, synthetic sRNAs suffer from low activity programmability and poor structural modularity. Moreover, natural sRNA backbone sequences may increase the possibility of unwanted recombination. Here, we present a bottom-up approach for creating structure defined single-stem loop small non-coding RNAs (ssl-sRNAs), which contain a standardized scaffold of a 7 bp-stem-4 nt-loop-polyU-tail and a 24 nt basing pairing region covering the first eight codons. Particularly, ssl-sRNA requires no independent Hfq-binding structure, as the polyU tail fulfills the roles of binding Hfq. A thermodynamic-based scoring model and a web server sslRNAD (http://www.kangzlab.cn/) were developed for automated design of ssl-sRNAs with well-defined structures and programmable activities. ssl-sRNAs displayed weak polar effects when regulating polycistronic mRNAs. The ssl-sRNA designed by sslRNAD showed regulatory activities in both Escherichia coli and Bacillus subtilis. A streamlined workflow was developed for the construction of customized ssl-sRNA and ssl-sRNA libraries. As examples, the E. coli cell morphology was easily modified and new target genes of ergothioneine biosynthesis were quickly identified with ssl-sRNAs. ssl-sRNA and its designer sslRNAD enable researchers to rapidly design sRNAs for knocking down target genes.